2021
DOI: 10.1093/brain/awab484
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic loss-of-function OBSCN variants predispose individuals to severe recurrent rhabdomyolysis

Abstract: Rhabdomyolysis is the acute breakdown of skeletal myofibres in response to an initiating factor, most commonly toxins and over exertion. A variety of genetic disorders predispose to rhabdomyolysis through different pathogenic mechanisms, particularly in patients with recurrent episodes. However, most cases remain without a genetic diagnosis. Here we present six patients who presented with severe and recurrent rhabdomyolysis, usually with onset in the teenage years; other features included a history of myalgia … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…However, unchanged E/A ratios even in older animals suggest no diastolic dysfunction in R4344Q mice. Intriguingly, there are reports of patients with a bi-allelic loss of obscurin that predispose these individuals to recurrent rhabdomyolysis 35 . Data from our obscurin knockout mice support the finding for the benign cardiac phenotype in affected patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, unchanged E/A ratios even in older animals suggest no diastolic dysfunction in R4344Q mice. Intriguingly, there are reports of patients with a bi-allelic loss of obscurin that predispose these individuals to recurrent rhabdomyolysis 35 . Data from our obscurin knockout mice support the finding for the benign cardiac phenotype in affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of obscurin Ig58-59 resulted in an arrhythmogenic cardiomyopathy in aged mice 33 . Patients with bi-allelic loss of obscurin were recently shown to predispose affected individuals to severe recurrent rhabdomyolysis 35 . Consequently, these patients are exercise intolerant.…”
Section: Introductionmentioning
confidence: 99%
“…cDNA studies, RNA-seq and western blotting showed substantial reduction in OBSCN expression and protein abundance in patient muscle, confirming that the likely pathomechanism was loss of obscurin function. Preliminary studies in patient myoblasts showed impaired SR refilling under stress conditions [30 ▪▪ ]. In further evidence that obscurin plays a role in Ca 2+ handling, Pierantozzi et al [31] showed slower sarcoplasmic reticulum Ca 2+ release and SERCA reuptake rates in Obscn null mouse myofibres.…”
Section: Novel Genetic Causes Of Rhabdomyolysismentioning
confidence: 98%
“…Triggers in some cases included exercise (even mild exercise) and/or heat; in two cases, the episodes appeared to occur spontaneously. Between episodes, serum CK levels were mildly elevated or within normal limits [30 ▪▪ ]. Three cases were elite level athletes in their youth, representing their sport at the national or international level.…”
Section: Novel Genetic Causes Of Rhabdomyolysismentioning
confidence: 99%
See 1 more Smart Citation